Consecutive isocyanide-based multicomponent reactions: synthesis of cyclic pentadepsipeptoids - Barreto, Angélica de Fátima S.; Vercillo, Otilie E.; Wessjohann, Ludger A.; Andrade, Carlos Kleber Z. (Beilstein Journal of Organic Chemistry, 2014)
The synthesis of six cyclic depsipeptoids inspired by the natural depsipeptide sansalvamide A is described. An efficient and fast synthetic strategy was developed using a combination of consecutive isocyanide-based multicomponent reactions (Ugi and Passerini reactions). This methodology can be used to access a variety of cyclic oligodepsipeptoids.
Keywords: depsipeptoids; multicomponent reactions; Passerini reaction; sansalvamide A; Ugi reaction